SAT0365 Secular trends in the incidence and prevalence of gout in denmark from 1995–2015: a nationwide register-based study. (12th June 2018) - Zobbe, K.; Prieto-Alhambra, D.; Cordzt, R.; Højgaard, P.; Hindrup, J.S.; Kristensen, L.E.; Dreyer, L.
Abstract : Background: Gout is percieved as the most prevalent inflammatory arthritis in the western world – but with great regional and ethnical variation. The incidence and prevalence is thought to be increasing but it's based on few population studies with limited calendar time periods.[ 1 We took advantage of the unique Danish health registries to examine the incidence and prevalence of gout in a nationwide cohort covering the last two decades. Objectives: To examine temporal trends in the incidence and prevalence of gout in the adult Danish population. Methods: Using the nationwide Danish National Patient Registry (DNPR), we calculated the incident rate of hospitalised gout patients (per 1 00 000 person-years) within each 1 year period from 1995 to 2015, and prevalence of gout requiring hospitalisation in 2000 and 2015. Additionally, the age- and gender-specific incidence rates of gout from 1995 to 2015 were calculated. Incidence rates were standardised according to the NORDCAN standard population. Confidence intervals (CI) were calculated according to a Poisson distribution. Both incidence rates based on diagnosis from all specialties and rheumatologists, respectively, were calculated. Results: In the 20 year study period we identified 45 685 newly diagnosed cases of gout. We found an increase in overall incidence, from 32.26/100, 000 [95%CI 30.7 to 33.1] in 1995 to 57.5/100, 000 [95%CI 55.6 to 59.5] in 2015(p<0.001). The age and sex specific incidence rates increased progressively with increasing age among both sexes, most markedly in patients aged >60 years. Similar trends were observed for cases diagnosed at rheumatology departments. We likewise observed an increase in the prevalence of gout from 0.29% [95%CI 0.29 to 0.30] in 2000 to 0.68% [95%CI 0.68 to 0.69] in 2015. Conclusions: We found a 1.8-fold increase in the incident rate of hospitalised gout patients in the period 1995–2015 in Denmark among both men and women. Similarly we found a 2.2-fold increase in the prevalence from 2000 to 2015. Further research is needed to elucidate the causes underlying the observed increase in the burden of gout in Denmark Reference: [1] Kuo C-F, Grainge MJ, Zhang W, et al. Global epidemiology of gout: prevalence, incidence, and risk factors. Nat Rev Rheumatol2015;11:649–62. doi:10.1038/nrrheum.2015.91 Disclosure of Interest: K. Zobbe: None declared, D. Prieto-Alhambra Grant/research support from: Amgen, Servier, and UCB, Speakers bureau: Amgen, R. Cordzt: None declared, P. Højgaard: None declared, J. Hindrup Consultant for: Berlin-Chemie Menarini and Grünenthal, L. E. Kristensen Grant/research support from: UCB, Biogen, Janssen pharmaceuticals, and Novartis, Speakers bureau: Pfizer, AbbVie, Amgen, UCB, BMS, Biogen, MSD, Novartis, Eli Lilly and Company, and Janssen pharmaceuticals, L. Dreyer: None declared